2001
DOI: 10.1111/j.1471-0528.2001.00202.x
|View full text |Cite
|
Sign up to set email alerts
|

Activin βA‐subunit and activin receptors in human myometrium at term and during labour

Abstract: Main outcome measures Tissue lysates of myometrium were analysed for activin A content using an enzymelinked immunosorbent assay and activin receptor proteins IA, IIA and IIB using Western hybridisation. Activin b A -subunit and activin receptors were localised in myometrium by immunohistochemistry. Results Activin A was detected by ELISA in non-pregnant, pregnant and labouring myometrium. Levels were signi®cantly higher in labouring myometrium. The three activin receptors IA, IIA and IIB were detected in all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Of particular interest, in spontaneous labour follistatin is significantly higher than antenatal levels even at a minimal cervical dilation (0-3 cm), indicating that follistatin is rising whilst the pre-labour stage of cervical ripening occurs. Although the study by Schneider-Kolsky et al (2001) showed neither activin b A subunits nor any of the three activin receptors were immunolocalised to the myometrial smooth muscle cells in active labour, perhaps the elevations noted in this study are due to the actions of the follistatin/activin complex or those of follistatin individually. The follistatin/activin complex or follistatin individually may be acting in concert with the increasing number of uterine myometrial heparan proteoglycans through labour in uterine remodelling essential for birth.…”
Section: Discussionmentioning
confidence: 86%
“…Of particular interest, in spontaneous labour follistatin is significantly higher than antenatal levels even at a minimal cervical dilation (0-3 cm), indicating that follistatin is rising whilst the pre-labour stage of cervical ripening occurs. Although the study by Schneider-Kolsky et al (2001) showed neither activin b A subunits nor any of the three activin receptors were immunolocalised to the myometrial smooth muscle cells in active labour, perhaps the elevations noted in this study are due to the actions of the follistatin/activin complex or those of follistatin individually. The follistatin/activin complex or follistatin individually may be acting in concert with the increasing number of uterine myometrial heparan proteoglycans through labour in uterine remodelling essential for birth.…”
Section: Discussionmentioning
confidence: 86%
“…Activin has a role in the regulation of cell differentiation and tissue remodelling, for instance, during wound repair 31 and in trophoblast invasion during establishment of the placental bed 32 . Activin A is secreted by trophoblast cells of placenta 33 and may have a role in regulating endothelial cell function 34–36 . Further examination of the interactions of activins with inhibins to control cell signalling and responses may provide further insight into the appropriate control of trophoblast invasion and remodelling of the vasculature in the placental bed and the regulation of endothelial cell function in the aetiology of hypertensive disease in pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Activin A levels in the peripheral maternal circulation do not increase in the last 3 weeks of pregnancy, remain unchanged during either spontaneous or induced labour and are similar in women delivering vaginally and in those delivered by elective Caesarean section (Schneider‐Kolsky et al ., 2000a). The same investigators also demonstrated, using immunohistochemistry, that activin receptors are not localized to pregnant myometrial smooth muscle, either before or during labour, suggesting that myometrial smooth muscle does not have target sites for activin A in late pregnancy or during labour (Schneider‐Kolsky et al ., 2001). It has also been shown that peripheral activin A levels cannot discriminate between women in threatened preterm labour who subsequently deliver preterm and those who did not (Coleman et al ., 2000).…”
Section: Placentamentioning
confidence: 99%
“…Pre‐eclampsia is characterized by widespread maternal vascular endothelial cell dysfunction (Roberts et al ., 1989a). It is therefore of interest that activin β A subunit and the activin receptors have been localized to both maternal (Schneider‐Kolsky et al ., 2001) and placental endothelial cells (Schneider‐Kolsky et al ., 2001). In addition, it has been shown that activin and follistatin may regulate some endothelial cell functions including proliferation and angiogenesis (McCarthy & Bicknell, 1993; Kozian et al ., 1997; Breit et al ., 2000).…”
Section: Placentamentioning
confidence: 99%